2003
DOI: 10.1128/aac.47.11.3531-3538.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Triclosan-Containing Rinse on the Dynamics and Antimicrobial Susceptibility of In Vitro Plaque Ecosystems

Abstract: Dental plaque microcosms were established under a feast-famine regimen within constant-depth film fermentors and exposed four times daily postfeeding to a triclosan (TR)-containing rinse (dentifrice) (TRD). This was diluted so that the antimicrobial content was 0.6 mg/ml. Microcosms were characterized by heterotrophic plate counts and PCR-denaturing gradient gel electrophoresis (DGGE) with primers specific for the V2-V3 region of the eubacterial 16S rRNA gene (rDNA). Dominant isolates and PCR amplicons were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 46 publications
(50 reference statements)
0
43
0
Order By: Relevance
“…Although the minimum inhibitory concentration (MIC) has been used for evaluating the antimicrobial activity, McBain et al (11) and McDonnell and Russel (12) observed that triclosan and chlorhexidine presented high antimicrobial potential against oral bacteria and, MIC obtained for triclosan was lower than the one obtained for chlorexidine. Pan et al (19), Riep et al (22), and Pitten and Kramer (20) evaluated the rate of microbial death after contact with antiseptic mouthrinses and observed that products containing essential oils were more effective.…”
Section: Resultsmentioning
confidence: 99%
“…Although the minimum inhibitory concentration (MIC) has been used for evaluating the antimicrobial activity, McBain et al (11) and McDonnell and Russel (12) observed that triclosan and chlorhexidine presented high antimicrobial potential against oral bacteria and, MIC obtained for triclosan was lower than the one obtained for chlorexidine. Pan et al (19), Riep et al (22), and Pitten and Kramer (20) evaluated the rate of microbial death after contact with antiseptic mouthrinses and observed that products containing essential oils were more effective.…”
Section: Resultsmentioning
confidence: 99%
“…PCRs were performed in sterile, nuclease-free, 0. (29,30). Gels were polymerized by adding tetramethylenediamide (50 l) and ammonium persulphate (1% [wt/vol], 100 l) immediately prior to pouring.…”
Section: Methodsmentioning
confidence: 99%
“…Glass slides were partially submerged in artificial saliva medium (40 ml) (24,25) supplemented with cysteine (26). The broth was inoculated with saliva from healthy volunteers, mixed briefly, and incubated statically at 37°C in an anaerobic cabinet for 48 h. Slides were then immersed in 1% slurries of test dentifrices (50 ml) for 60 s and gently agitated.…”
Section: Methodsmentioning
confidence: 99%